2015
DOI: 10.1038/ncomms7426
|View full text |Cite
|
Sign up to set email alerts
|

Housing temperature-induced stress drives therapeutic resistance in murine tumour models through β2-adrenergic receptor activation

Abstract: Cancer research relies heavily on murine models for evaluating the anti-tumour efficacy of therapies. Here we show that the sensitivity of several pancreatic tumour models to cytotoxic therapies is significantly increased when mice are housed at a thermoneutral ambient temperature of 30 °C compared with the standard temperature of 22 °C. Further, we find that baseline levels of norepinephrine as well as the levels of several anti-apoptotic molecules are elevated in tumours from mice housed at 22 °C. The sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
145
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 133 publications
(152 citation statements)
references
References 69 publications
6
145
1
Order By: Relevance
“…We also found that NE levels were higher in tumors of mice at ST compared to TT [44]. In more recent work, M. Bucsek et al (manuscript in preparation) find that, at ST, tumor growth can be significantly delayed by administration of propranolol (a b-adrenergic receptor antagonist), and 30-32 8C.…”
Section: Feeling Cold Tumor Immunology and Therapeutic Efficacy -Nosupporting
confidence: 67%
See 4 more Smart Citations
“…We also found that NE levels were higher in tumors of mice at ST compared to TT [44]. In more recent work, M. Bucsek et al (manuscript in preparation) find that, at ST, tumor growth can be significantly delayed by administration of propranolol (a b-adrenergic receptor antagonist), and 30-32 8C.…”
Section: Feeling Cold Tumor Immunology and Therapeutic Efficacy -Nosupporting
confidence: 67%
“…At thermoneutrality the mechanisms underlying successful antitumor immune responses may differ from those mechanisms at ST. For example, recent evidence shows that exposure of mice to mild cold stress (ST) affects the differentiation pathway of macrophages such that IL-4-mediated 'alternative activation' of adipose tissue macrophages (which secrete NE) occurs to promote thermogenesis in BAT and lipolysis in WAT [43]. These alternatively activated macrophages could themselves be another source of immunosuppression.We also found that NE levels were higher in tumors of mice at ST compared to TT [44]. In more recent work, M. Bucsek et al (manuscript in preparation) find that, at ST, tumor growth can be significantly delayed by administration of propranolol (a b-adrenergic receptor antagonist), and 30-32 8C.…”
supporting
confidence: 67%
See 3 more Smart Citations